GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

It is currently 25 Feb 2020, 18:50

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
e-GMAT Representative
User avatar
V
Joined: 04 Jan 2015
Posts: 3256
If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......  [#permalink]

Show Tags

New post Updated on: 26 Jun 2019, 02:42
00:00
A
B
C
D
E

Difficulty:

  45% (medium)

Question Stats:

59% (01:49) correct 41% (02:10) wrong based on 70 sessions

HideShow timer Statistics


Originally posted by EgmatQuantExpert on 19 Jun 2019, 05:44.
Last edited by EgmatQuantExpert on 26 Jun 2019, 02:42, edited 1 time in total.
Intern
Intern
avatar
B
Joined: 27 Jun 2018
Posts: 14
Re: If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......  [#permalink]

Show Tags

New post 19 Jun 2019, 10:30
3
1
If one root of the quadratic equation is \(2+\sqrt{3},\)the other root is \(2-\sqrt{3}.\)Now, sum of roots = a = \(2+\sqrt{3}+2-\sqrt{3}\) = 4
product of roots = b = \((2+\sqrt{3})(2-\sqrt{3})\)= \(2^2 -{\sqrt{3}}^2\) = 4-3 = 1
Hence, a + b = 4 + 1 = 5 (Option E)
GMAT Club Legend
GMAT Club Legend
User avatar
V
Joined: 18 Aug 2017
Posts: 5918
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)
GMAT ToolKit User Reviews Badge CAT Tests
Re: If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......  [#permalink]

Show Tags

New post 19 Jun 2019, 10:36
giving a try
\(x^2 - ax + b = 0\),
so
we have ; (2+√3)^2- (2+√3)a+b=0
now value of a,b has to be such that eqn is 0
so let a= 4 and b=1
we get
7+4√3-8-4√3+1=0
sufficient
a+b = 4+1 ; 5
IMO E

EgmatQuantExpert wrote:
If 2 + √3 is one root of the equation, \(x^2 - ax + b = 0\), where a, b are positive numbers, then what is the value of a + b?

    (A) 0
    (B) 1
    (C) 2√3
    (D) 4
    (E) 5

Image
e-GMAT Representative
User avatar
V
Joined: 04 Jan 2015
Posts: 3256
Re: If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......  [#permalink]

Show Tags

New post 26 Jun 2019, 02:44

Solution


Given:
    • 2 + √3 is one root of the quadratic equation, \(x^2 - ax + b = 0\)
    • a, b are positive numbers

To find:
    • The value of a + b

Approach and Working Out:
    • We are given that 2 + √3 is one root of the quadratic equation, \(x^2 - ax + b = 0\)
    • And, we know that, if a +√ b is one root of a quadratic equation, then the other root will be a - √b.
      o Thus, 2 + √3, and 2 - √3 are the two roots

    • Now, from the given quadratic equation, \(x^2 - ax + b = 0\)
      o Sum of the roots = -(-a) = a = (2 + √3) + (2 - √3) = 4
      o Product of the roots = b = (2 + √3) * (2 - √3) = 4 – 3 = 1

    • Therefore, a + b = 4 + 1 = 5

Hence, the correct answer is Option E.

Answer: E


Image

_________________
VP
VP
avatar
V
Joined: 20 Jul 2017
Posts: 1332
Location: India
Concentration: Entrepreneurship, Marketing
WE: Education (Education)
Re: If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......  [#permalink]

Show Tags

New post 26 Jun 2019, 03:53
EgmatQuantExpert wrote:
If 2 + √3 is one root of the equation, \(x^2 - ax + b = 0\), where a, b are positive numbers, then what is the value of a + b?

    (A) 0
    (B) 1
    (C) 2√3
    (D) 4
    (E) 5

Image


If 1 root is x + sqrt(y)
The other root will be x - sqrt(y)

So other root is 2 - 3^1/2

a = sum of roots = 4
b = product of roots = 4 - 3 = 1

a + b = 5

Option E

Posted from my mobile device
GMAT Club Bot
Re: If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......   [#permalink] 26 Jun 2019, 03:53
Display posts from previous: Sort by

If 2 + √3 is one root of the equation, [m]x^2 - ax + b = 0[/m], ......

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne